Not as we thought: Transitions into the orchestral workplace - Bennett, Dawn (Australian Society for Music Education Inc, 2007)
Winning an orchestral position is cause for celebration. The result of long-term, intensive study and, often, countless auditions, new players are understandably enthusiastic about their future. But are the realities of orchestral life what they had expected? Building on previous research with established orchestral players, this paper discusses a case study within a larger ethnographic study of the orchestral workplace. The case study discussed here was intended to develop a better understanding of the issues facing new players, and involved casual and permanent orchestral players in their first year of orchestral work. Results indicated a level of disappointment with orchestral life. Although many aspects of this disappointment had been voiced by established players in earlier studies, the rapidity with which negativity was voiced by new players was surprising, and suggests that more could be done to support them.